Wet coprecipitation preparation of perovskite-type iron manganite nano powder pure phase using nitrate precursors: structural, opto-electronic, morphological and photocatalytic activity for degradation of Nile blue dye - Habibi, Mohammad Hossein; Mosavi, Vala (Journal of materials science. Materials in electronics, 2017)
A pure phase of iron manganite nano powder has been prepared by the wet coprecipitation route using nitrate precursors subject to heat treatment at 650 °C for 4 h in air. The structural, opto-electronic, thermal and morphological properties of iron manganite nano powder were investigated by X-ray diffraction (XRD), field emission scanning electron microscopy (FESEM), energy-dispersive X-ray spectroscopy (EDX), and UV–Vis diffuse reflectance spectroscopy (UV–Vis DRS). XRD results showed that a pure phase nano powder iron manganite with perovskite-type structure is formed. FESEM results showed that an average size of the iron manganite nano particles at about 64 nm with a narrow particle size distribution. UV–vis DRS reveal the optical band gap of 1.901 eV (652 nm) with a strong absorption at visible region of solar light. The photcatalytic activity of pure phase nano powder iron manganite perovskite catalyst displayed an excellect activity in degradation of Nile blue organic dye with 95% efficiency and 86% TOC removal in 80 min of irradiation.